Dental healthcare reforms in Germany and Japan: A comparison of statutory health insurance policy - Mayumi Nomura (Elsevier, 2008)
This article aims to compare statutory health insurance policy during the dental healthcare reforms in Germany and Japan. Germany and Japan have categorized their statutory health insurance systems. People in both countries have been provided with a wide coverage of dental treatment and prosthetics. To compare the trends of the indicators of oral healthcare systems over time, it has been suggested that the strategic allocation of dental expenditure is more important than the amount of expense. German dental healthcare policy has shifted under political and socio-economic pressures towards a cost-effective model. In contrast, Japanese healthcare reforms have focused on keeping the basic statutory health insurance scheme, whereby individuals share more of the cost of statutory health insurance. As a result, Germany has succeeded in dramatically decreasing the prevalence of dental caries among children. On comparing the dental conditions of both countries, the rate of decline in replacement of missing teeth among adults and the elderly in Germany and Japan has been interpreted as indicating the price-conscious demands of prosthetics. The difference in the decline of DMFT in 12-year-olds in Germany and Japan could be described as being due to the dental health insurance policy being shifted from treatment-oriented to preventive-oriented in Germany. These findings suggest that social health insurance provides people with equal opportunity for dental services, and healthcare reforms have improved people's oral health. A mixed coverage of social health insurance coverage for dental care should be reconsidered in Japan.